2012
DOI: 10.1017/s1755691013000364
|View full text |Cite
|
Sign up to set email alerts
|

Cranial anatomy of the Late Triassic phytosaurMachaeroprosopus, with the description of a new species from West Texas

Abstract: The skull anatomy of a new species of the phytosaur Machaeroprosopus is described for the first time on the basis of two specimens from the Upper Triassic Cooper Canyon Formation of Texas. Additional information is provided by a third specimen referred to Machaeroprosopus sp. A paranasal bone, an additional paired element of the narial region, is identified. Important new data are presented for the braincase, including the morphology of the epipterygoid and presphenoid, an anterior process of the prootic, an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
56
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(72 citation statements)
references
References 49 publications
14
56
2
Order By: Relevance
“…The deeply recessed nature of the fenestra ovalis of Mesosuchus is similar to Stenaulorhynchus (Benton, 1983) and Teyumbaita (Montefeltro, Langer & Schultz, 2010), but contrasts with Hyperodapedon (Benton, 1983), and Rhynchosaurus (Benton, 1990). Outside Rhynchosauria, recessed fenestrae are found in the archosauriforms Erythrosuchus (Gower, 1997) and Sarmatosuchus (Gower & Sennikov, 1997), but also in phytosaurs (Hungerbühler et al, 2012). The implications of a recessed fenestra ovalis are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The deeply recessed nature of the fenestra ovalis of Mesosuchus is similar to Stenaulorhynchus (Benton, 1983) and Teyumbaita (Montefeltro, Langer & Schultz, 2010), but contrasts with Hyperodapedon (Benton, 1983), and Rhynchosaurus (Benton, 1990). Outside Rhynchosauria, recessed fenestrae are found in the archosauriforms Erythrosuchus (Gower, 1997) and Sarmatosuchus (Gower & Sennikov, 1997), but also in phytosaurs (Hungerbühler et al, 2012). The implications of a recessed fenestra ovalis are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…This is a node‐based taxon using the type species of each currently recognized (Hungerbühler et al . ) mystriosuchin (= pseudopalatine) genus as an internal specifier. These taxa have been used as specifiers to retain consistency in composition as much as possible with the traditional ‘Pseudopalatinae’, but follow recommendations for phylogenetic nomenclature in prioritizing the use of type species in definitions.…”
Section: Discussionmentioning
confidence: 99%
“…The monophyly of the newly diagnosed Machaeroprosopus with respect to ‘ Redondasaurus ’ was tested by Hungerbühler et al (2013); the two species of ‘ Redondasaurus ’ were previously found to nest paraphyletically within Machaeroprosopus (Hungerbühler, Chatterjee & Cunningham, 2003). The primary purpose of the analysis was, however, to test the phylogenetic position of the newly described species Machaeroprosopus lottorum .…”
Section: Introductionmentioning
confidence: 99%